Learning how to learn from social feedback: The origins of early vocal development. Issue 2 (5th July 2022) - Elmlinger, Steven L.; Schwade, Jennifer A.; Vollmer, Laura; Goldstein, Michael H.
Abstract: Infants' prelinguistic vocalizations reliably organize vocal turn‐taking with social partners, creating opportunities for learning to produce the sound patterns of the ambient language. This social feedback loop supporting early vocal learning is well‐documented, but its developmental origins have yet to be addressed. When do infants learn that their non‐cry vocalizations influence others? To test developmental changes in infant vocal learning, we assessed the vocalizations of 2‐ and 5‐month‐old infants in a still‐face interaction with an unfamiliar adult. During the still‐face, infants who have learned the social efficacy of vocalizing increase their babbling rate. In addition, to assess the expectations for social responsiveness that infants build from their everyday experience, we recorded caregiver responsiveness to their infants' vocalizations during unstructured play. During the still‐face, only 5‐month‐old infants showed an increase in vocalizing (a vocal extinction burst) indicating that they had learned to expect adult responses to their vocalizations. Caregiver responsiveness predicted the magnitude of the vocal extinction burst for 5‐month‐olds. Because 5‐month‐olds show a vocal extinction burst with unfamiliar adults, they must have generalized the social efficacy of their vocalizations beyond their familiar caregiver. Caregiver responsiveness to infant vocalizations during unstructured play was similar for 2‐ and 5‐month‐olds. Infants thus learn the social efficacy of their vocalizations between 2 and 5 months of age. During this time, infants build associations between their own non‐cry sounds and the reactions of adults, which allows learning of the instrumental value of vocalizing. Abstract : Learning to expect that one's own voice influences the behavior of others is a foundational skill in communicative development. We measured 2‐ and 5‐month‐old infants' expectation that their babbling elicits responses from adults. To test developmental changes in this expectation, we assessed vocalizations of 2‐ and 5‐month‐old infants in a still‐face interaction with an unfamiliar adult. The paradigm allowed us to measure infants' strength of expectation for influencing others with their babble. During the still‐face, infants who have learned the social efficacy of vocalizing increase their babbling rate. The curve in the plot depicts the vocal extinction burst (VEB), in which extinction (i.e., cessation) of social responsiveness during the still face period results in a burst of infant vocalizing. The red vertical dash indicates peak vocalizing. During the still‐face, only 5‐month‐old infants showed an increase in vocalizing, indicating that they learned to expect adult responses to their vocalizations. Caregiver responsiveness predicted the magnitude of the vocal extinction burst for 5‐month‐olds. Because 5‐month‐olds show a vocal extinction burst with unfamiliar adults, they have generalized the social efficacy of their vocalizations beyond their familiar caregiver. Caregiver responsiveness to infant vocalizations during unstructured play was similar for 2‐ and 5‐month‐olds. Infants thus learn the social efficacy of their vocalizations between 2 and 5 months of age. During this time, infants build associations between their own babbling and the reactions of adults, which allows learning of the instrumental value of vocalizing.